Potentiality of Genetic Manipulation for Increasing Biomass Production in Eucalyptus - Kapoor, M. L.; Sharma, V. K. (Indian Forester, 1984)
Biomass of Eucalyptus can be increased through genetic manipulation. Improved material created through hybridization, polyploidy and mutagenesis has been compared with different controls. Superiority of experimentally produced hybrids, allotriploid and mutants calculated at the age of 30, 10 and 10 months respectively on height, diameter, tolal biomass and volume is very high in comparison to their respective controls. Eucalyptus seems to be a very good material for breeding purposes having good scope for improvement in the genetic traits.